1994
DOI: 10.1111/j.1476-5381.1994.tb13192.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacology of analogues of S‐nitroso‐N‐acetyl‐dl‐penicillamine on human platelets

Abstract: The effects of two new analogues of S‐nitroso‐N‐acetyl‐dl‐penicillamine (SNAP), S‐nitroso‐N‐formyl‐dl‐penicillamine (SNFP) and S‐nitroso‐dl‐penicillamine (SNPL), on platelet function were examined in vitro. SNAP and its analogues were potent inhibitors of platelet aggregation and inducers of disaggregation. All compounds inhibited fibrinogen binding to platelets. They also decreased the release of P‐selectin from platelets. Both inhibition of fibrinogen binding and release of P‐selectin correlated with an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…3-Morpholino-sydnonimine (SIN-1) an active metabolite of the anti-anginal drug molsidomine, has been shown to release NO together with superoxide anion (02-) (Feelisch, 1991;Hogg et al, 1992). Recently, some chemically different compounds have been reported to release NO directly or indirectly (Maragos et al, 1991;Feelisch et al, 1992;Mulsch et al, 1993;Medana et al, 1994;Kita et al, 1994;Salas et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…3-Morpholino-sydnonimine (SIN-1) an active metabolite of the anti-anginal drug molsidomine, has been shown to release NO together with superoxide anion (02-) (Feelisch, 1991;Hogg et al, 1992). Recently, some chemically different compounds have been reported to release NO directly or indirectly (Maragos et al, 1991;Feelisch et al, 1992;Mulsch et al, 1993;Medana et al, 1994;Kita et al, 1994;Salas et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, apyrase and 2-MeSAMP did not exert significant effects on platelet microaggregation, indicating that release of ADP from platelets does not significantly contribute to generation of platelet microaggregates under the experimental conditions used. Prostacyclin and NO are important platelet inhibitors generated from the endothelium that synergize to regulate platelet activation; 31 therefore, prostacyclin and two NOreleasing compounds, GSNO and SNAP, known to inhibit platelet aggregation, 29,30 were also tested. Prostacyclin was not only able to inhibit platelet aggregation but also caused disaggregation as monitored in real-time by the device, an effect similar to that measured by light aggregometry.…”
Section: Pharmacology Of Fibrinogen-induced Platelet Microaggregationmentioning
confidence: 99%
“…Since nitric oxide (NO) mediates major inhibitor pathways and regulates platelet GPIIb/IIIa receptor function, [26][27][28] we tested the effects of platelet-inhibitory NO-releasing agents such as SNAP 29 and GSNO. 30 Both compounds inhibited platelet aggregation, as reflected by reduced changes in f and D compared with the control and corroborated by optical microscopy (SNAP Dp=0.0005; SNAP fp=0.0011 and GNSO Dp=0.0005; fp=0.0017, n=4).…”
mentioning
confidence: 99%
“…These authors observed that PN (20 M-200 M), but not of decomposed PN, when added to washed platelet suspensions produced concentration-dependent increases in aggregation when measured by plateletionized calcium aggregometer [22]. The additions of platelet aggregation inhibitors such as SNAP, prostacyclin, or indomethacin [228,229] to the washed platelet suspensions had no significant effect on platelet aggregation induced by PN [22]. The addition of PN could also completely reverse the inhibitory effects of SNAP on collagen-induced platelet aggregation, whereas PN would significantly reverse (~50%) the antiaggregatory effects of indomethacin and of prostacyclin [22].…”
Section: Anti-platelet Aggregation Effects Of Peroxynitritementioning
confidence: 99%